Phenotypic, molecular characterization, antimicrobial susceptibility and draft genome sequence of Corynebacterium argentoratense strains isolated from clinical samples. (March 2016) - Fernández-Natal, I.; Sáez-Nieto, J.A.; Rodríguez-Lázaro, D.; Valdezate-Ramos, S.; Parras-Padilla, T.; Medina, M.J.; Rodríguez-Pollán, R.H.; Blom, J.; Tauch, A.; Soriano, F.
Abstract: During a 12-year period we isolated five Corynebacterium argentoratense strains identified by phenotypic methods, including the use of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF) and 16S rRNA gene sequencing. In addition, antimicrobial susceptibility was determined, and genome sequencing for the detection of antibiotic resistance genes was performed. The organisms were isolated from blood and throat cultures and could be identified by all methods used. All strains were resistant to cotrimoxazole, and resistance to β-lactams was partly present. Two strains were resistant to erythromycin and clindamycin. The draft genome sequences of theses isolates revealed the presence of the erm (X) resistance gene that is embedded in the genetic structure of the transposable element Tn 5423. Although rarely reported as a human pathogen, C. argentoratense can be involved in bacteraemia and probably in other infections. Our results also show that horizontal transfer of genes responsible for antibiotic resistance is occurring in this species.